2021
DOI: 10.3390/rs13224602
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Analyzing Yield Gap in Africa through Soil Attribute Best Management Using Remote Sensing Approaches: A Review

Abstract: Africa has the largest population growth rate in the world and an agricultural system characterized by the predominance of smallholder farmers. Improving food security in Africa will require a good understanding of farming systems yields as well as reducing yield gaps (i.e., the difference between potential yield and actual farmer yield). To this end, crop yield gap practices in African countries need to be understood to fill this gap while decreasing the environmental impacts of agricultural systems. For inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 99 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…This reviewing study indicates that recent studies in Africa are increasingly adopting remote sensing based spatial prediction approach in comparison to other tools for monitoring the variation of soil and crops NPK content. This is consistent with a recent study [34] that reported the same increasing trend regarding the use of remote sensing for field studies in Africa. The presented case studies showcased a difference in costeffectiveness and performance between remote sensing approach and traditional soil and crop sampling methods.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This reviewing study indicates that recent studies in Africa are increasingly adopting remote sensing based spatial prediction approach in comparison to other tools for monitoring the variation of soil and crops NPK content. This is consistent with a recent study [34] that reported the same increasing trend regarding the use of remote sensing for field studies in Africa. The presented case studies showcased a difference in costeffectiveness and performance between remote sensing approach and traditional soil and crop sampling methods.…”
Section: Resultssupporting
confidence: 93%
“…Despite its outstanding performance, hyperspectral imaging has been utilized comparatively less in African operational agricultural applications in the past few decades. This might be explained by the high cost of imagery and various other technical and practical challenges (e.g., access to the specialized software needed and the skills to process this the large data volume) [34]. This might also explain why most of the papers reviewed in this study used spectroscopy instead of hyperspectral imaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the gap in research work output in Asia was larger than that in Europe (Goga et al, 2019;Chen et al, 2020;Mikhaylov et al, 2021). Moreover, the continental gap in Africa has obviously narrowed due to the increasing investment in scientific research in the current decade (Khechba et al, 2021;Mngadi et al, 2022;Sebola, 2022). Regarding the continental gap between Asia and other continents, the gap between Asia and Africa was the largest, and the gap between Asia and Europe was the smallest (Figure 5A), showing that the gap between the two continents with high research output was not large.…”
Section: Nomentioning
confidence: 99%
“…In the Mediterranean, for example, a gap of 41% and 29% is recorded in Morocco for rainfed and irrigated wheat, respectively [21], while in Spain a gap of 49% to 66% is observed for rainfed wheat [22]. In addition, yield gap analysis and the importance of finding the main reasons that limit actual yields has been widely studied around the world [21,[23][24][25] and increasingly in Africa [26]. Many agronomic causes are often behind these deficits [27], and they can be lack of nitrogen fertilizer [25,27,28], limited number of spikes per hectare [29], inappropriate sowing date [25,28], soil fertility level [25], biotic stresses [30], water stress [22], low seeding rate, summer fallow, and tillage [31], etc.…”
Section: Introductionmentioning
confidence: 99%